Age-related gait adaptations: analysis of temporal gait parameters and variability, and muscle activation across flat vs. uneven surfaces in young, middle-aged, and older adults - Inns, Thomas B.; Pina, Ilaria; Macgregor, Lewis James; Dudchenko, Paul A.; Crockett, Rachel A.; Hunter, Angus Murray (Frontiers in Aging, 2025)
IntroductionWalking is a common physical activity among older adults, but it becomes more complex with age due to increased demands on motor control and attention, particularly when walking surface is uneven. Age-related changes in walking gait, especially after 70, can lead to restricted mobility and higher mortality risk. This study investigated age-related differences in gait parameters and muscle activation across young (18–39 years), middle-aged (40–59 years), and older adults (60+ years) on flat and uneven surfaces.MethodsEighty-three healthy adults participated in the study. Variability in double support, stance, swing, and stride times; and muscle activity were assessed during walking on both surface types and used as dependent variables.ResultsAnalysis showed that older adults adopted a more cautious walking strategy, characterized by longer double support and shorter swing phases, regardless of the surface. Muscle activation patterns indicated increased demands on the plantar flexors and knee extensors in older adults. Walking on uneven surfaces increased gait variability across all age groups.ConclusionThese findings highlight age-specific walking adaptations related to muscle activation. Understanding these adaptations is crucial for developing targeted interventions to enhance walking performance and reduce fall risks, especially in older adults. The study underscores the importance of assessing gait under various conditions to comprehensively capture age-related differences.